2015
DOI: 10.1111/jam.12788
|View full text |Cite
|
Sign up to set email alerts
|

Aerosol-phase activity of iodine captured from a triiodide resin filter on fine particles containing an infectious virus

Abstract: This study shows that disinfection by filter-bound iodine in the aerosol phase is too slow to be clinically significant in individual respiratory protection, but that it might be of benefit to limit airborne transmission of infections in enclosed areas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Previous in vitro studies conducted by various investigators and air purification products manufacturer reported that incorporating poly (styrene-4-[trimethylammonium] methyl triiodide) (PSTI), an oxidative agent to the filter layer provides 2-log increase in viable removal efficiency (VRE) compare to the standard filter layers (14)(15)(16)(17)(18). Others' work suggested that the exposure to the treated resin shortened the half-life for deactivation by at least half; quenching experiments in which the aerosols were trapped in thiosulfate medium showed complete loss of effect by the iodine (19).…”
Section: Introductionmentioning
confidence: 99%
“…Previous in vitro studies conducted by various investigators and air purification products manufacturer reported that incorporating poly (styrene-4-[trimethylammonium] methyl triiodide) (PSTI), an oxidative agent to the filter layer provides 2-log increase in viable removal efficiency (VRE) compare to the standard filter layers (14)(15)(16)(17)(18). Others' work suggested that the exposure to the treated resin shortened the half-life for deactivation by at least half; quenching experiments in which the aerosols were trapped in thiosulfate medium showed complete loss of effect by the iodine (19).…”
Section: Introductionmentioning
confidence: 99%